Conceptualize, design, simulate and develop a contact tracing scheme based on the Android platform - Woon, Tse Liang (Nanyang Technological University, 2021)
Bluetooth Low Energy (BLE) is a low power consumption wireless technology. It enables devices to communicate within a short range. There are two roles in which the devices would play, the central or peripheral. The device which plays the central role is the one which actively look for those in the peripheral role. While the device which plays the peripheral role is one which is one which advertises that it is available for connection. A type of device which makes use of this technology are BLE beacons. BLE beacons are small devices which can be placed in certain locations to advertise various data such as promotions when a customer walks into a store. These beacons have a certain identifier linked to it such that when an app that is already installed on the user device picks it up, it will be able to obtain the data. In this project, an android application which uses the BLE becaon technology for contact tracing will be developed. The method of contact tracing is for people to check in to the locations that they have visited. The application would have two functions: scanning for beacons and transmitting as a beacon. Upon detecting the beacon, an action to check-in would be triggered. This report will focus on the research and development of the android application.